STRUGGLE AS SEEN IN OWENS’ WHERE THE CRAWDADS SING - FIONNY I GUSTAMAN; IMELDA S LOLOWANG (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this study is to reveal the struggles in the novel Where The Crawdads Sing by Delia Owens (2019). In conducting the study, the writers delimit only in analysing the struggles of the main character in the novel. The design of this study is qualitative method because all of the data are in the form of words and quotations rather than numbers and the approach used Reader-Response, It focuses on the process of struggles of the main character that produces the result. The writers find that three forms of struggle. They accept the facts of life, achieve the goals, and get affection. The implication of this study is to enrich the knowledge of the writers and the readers about the main character’s struggles that reflected in Owens’ Where The Crawdads Sing. Moreover, it can be a reference for the students of English Department who are attracted to observe the similar research. Therefore, this research can conclude the novel, Where The Crawdads Sing, to show the forms of the struggle of the main character.